Serum Pentraxin 3 Levels are Associated with the Complexity and Severity of Coronary Artery Disease in Patients with Stable Angina Pectoris. (February 2013) - Karakas, Mehmet Fatih; Buyukkaya, Eyup; Kurt, Mustafa; Motor, Sedat; Akcay, Adnan Burak; Buyukkaya, Şule; Karakas, Esra; Bilen, Perihan; Sen, Nihat
Background: Atherosclerosis is a complex inflammatory process in which inflammatory markers are involved. Although pentraxin 3 (PTX-3), a newly identified inflammatory marker, was associated with adverse outcomes in stable angina pectoris, no association between PTX-3 and the complexity of coronary artery disease (CAD) has been reported. Thus, the aim of the present study was to assess the association between the level of PTX-3 and the complexity and severity of CAD assessed with SYNTAX and Gensini scores in patients with stable angina pectoris. Methods: The study population consisted of 2 groups: 161 patients with anginal symptoms and evidence of ischemia who underwent coronary angiography and 50 age- and sex- matched control subjects without evidence of ischemia were included. Patients were grouped into 3 groups according to the complexity and severity of coronary lesions assessed by the SYNTAX score (30 patients with a SYNTAX score of 0 were excluded). Serum PTX-3 and high-sensitivity C-reactive protein (hs-CRP) levels were measured. Results: The PTX-3 levels demonstrated an increase from low to high SYNTAX groups ( r = 0.72, P < 0.001). Whereas the low SYNTAX group had statistically significantly higher PTX-3 levels when compared with the control group (0.50 ± 0.01 vs 0.24 ± 0.01 ng/mL, P < 0.001), the hs-CRP levels were not different (0.81 ± 0.42 vs 0.86 ± 0.53 mg/dL, P = 0.96). However, the intermediate SYNTAX group had higher hs-CRP levels compared with the low SYNTAX group (1.3 ± 0.66 vs 0.86 ± 0.53 mg/dL, P = 0.002). Serum PTX-3 levels and hs-CRP levels were correlated with the SYNTAX scores and Gensini scores (for SYNTAX: r = 0.87 [ P < 0.001] and r = 0.36 [ P = 0.01]; for Gensini: r = 0.75 [ P < 0.001] and r = 0.27 [ P = 0.002], respectively), and according to the results of univariate and multivariate analyses, for "intermediate and high" SYNTAX scores, age, diabetes mellitus, low-density lipoprotein cholesterol, hs-CRP, and PTX-3 were found to be independent predictors, whereas for the presence of "high" SYNTAX score only PTX-3 was found to be an independent predictor. The receiver operating characteristic curve analysis further revealed that the PTX-3 level was a strong indicator of high SYNTAX score with an area under the curve of 0.91 (95% confidence interval, 0.86-0.96). Conclusions: Pentraxin 3, a novel inflammatory marker, was more tightly associated with the complexity and severity of CAD than hs-CRP and was found to be an independent predictor for high SYNTAX score.